A Insights from literature analysis : optimal sunscreen use decreases Melasma incidence in women living in tropical climates - Damayanti, Lina; Pradini, Astri; Salsabila, Mitha (ACTA Medical Health Sciences, 2024)
Melasma is a hyperpigmented patch that is generally found on the face, especiallyon the cheeks, chin, upper lip, and can extend to the neck. The color of hyperpigmentation in melasma varies, generally from light brown to black with an irregular shape. Melasma is often found in countries with tropical climates with skin types III-V. This happens because countries with these climates are exposed to more sunlight. To prevent melasma, it is recommended to use sunscreen to reduce excessive UV exposure to the skin. It is important to use sunscreen optimally in order to reduce the incidence of melasma. The effect of excessive UV exposure to skin, including melasma, can be reduced by applying sunscreen on the regular basis. This literature review used four databases (Google scholar, PUBMED, NCBI and PERDOSKI) and relevant keywords such as "melasma" and "sunscreen" to find the source of articles published in 2010 to 2022. A total of 142 articles in Indonesian and English were found. After selecting based on inclusion and exclusion criteria, 14 relevant articles were obtained and will be discussed in this literature review. The result of this literature review show a significant relationship between optimal use of sunscreen and the incidence of melasma in women from countries with tropical climates, especially in Asia. Melasma is most commonly found in women with Fitzpatrick skin types III-V and more likely to occur between ages 25-60 years. Patients with melasma who used sunscreen optimally, by applying it every 2 hours, showed a decrease in the degree of severity of melasma compared to those who did not repeat the use of sunscreen. The conclusion can be strengthened more straightforward. For example, applying sunscreen every 2h can significantly decrease the incidence of melasma. DOI : 10.35990/amhs.v2n3.p148-156 REFERENCES Rodrigues M, Pandya AG. Hypermelanoses. In: Kang S, Amagai M, Bruckner AL, Enk AH, Margolis DJ, McMichael AJ, et al, editors. Fitzpatrick’s Dermatology. 9th ed. New York: McGraw Hill; 2019. p. 1379-81. Handel AC, Miot LDB, Miot HA. Melasma: a clinical and epidemiological review. An Bras Dermato. 2014;5:772. Sarkar R, Arora P, Garg VK, Sonthalia S, Gokhale N. Melasma Update. Indian Dermatology Online Journal. 2014;5(4):426. Apriliyani PY. Hubungan Antara Pemakaian Tabir Surya Dengan Derajat Keparahan Melasma (Skor MASI) Pada Wanita di Kec. Grogol-Sukoharjo. Surakarta: Fakultas Kedokteran Universitas Muhammadiyah Surakarta; 2017. Shankar KDSR, Somani VK, Kohli M, Sharad J, Ganjoo A, Kandhari S, et al. A cross-sectional, multicentric clinico-epidemiological study of melasma in India. Dermatologic Therapy. 2014;3:71-81. Purba RA. Gambaran Faktor-Faktor Risiko Timbulnya Melasma di Poliklinik Kulit dan Kelamin RSU Royal Prima dan Murni Teguh Memorial Hospital Kota Medan Pada Bulan Desember 2018-Januari 2019. Medan: Fakultas Kedokteran Universitas HKBP Nommesen Medan; 2019. Waskita TW. Hubungan antara riwayat pemakaian tabir surya dengan derajat keparahan melasma. Cimahi: Fakultas Kedokteran Universitas Jenderal Achmad Yani; 2018. Umborowati MA, Rahmadewi. Studi Retrospektif: Diagnosis dan Terapi Pasien Melasma. Berkala Ilmu Kesehatan Kulit & Kelamin. 2014;26:56-61. Krupa S, Devasthanam SR, et al. A cross-sectional, multicentric clinico-epidemiological study of melasma in India. 2014;4.1:71-81. Rattananukrom T, Suchonwanit P, Thadanipon K, Vachiramon V. A Comparative Study of Dermatoscopic Features of Melasma and Hori's Nevus in Asian Patients. J Clin Aesthet Dermatol. 2022;15(3):16-20. Bhattarai S, Pradhan K, Sharma S, Rajouria EA. Clinical patterns and epidemiological characteristics of melasma in a tertiary care hospital of Nepal. Pigment International. 2017;4(1):35. Wu MX, Antony R, Mayrovitz HN. Melasma: A Condition of Asian Skin. Cureus. 2021;13(4). Jha AK, Karki S. Vitiligo and melasma: a psychosocial-cosmetic challenge in context of south Asian countries. J Pigment Disord. 2015. Harumi O, Goh CL. The effect of melasma on the quality of life in a sample of women living in Singapore. The Journal of Clinical and Aesthetic Dermatology. 2016 Jan;9(1):21. Setyawati NK. Insiden dan Profil Melasma di Rumah Sakit Umum Pusat Sanglah Denpasar Periode Januari 2014 Sampai Desember 2014. E-Jurnal Medika Udayana. 2019 Apr 18;8(2). Lahida SP. Hubungan riwayat pemakaian tabir surya dengan kejadian melasma pada wanita usia 25-45 tahun. Jakarta: Trisakti; 2018. Prabawaningrum CD. Hubungan Riwayat Pemakaian Tabir Surya dengan Kejadian Melasma. Surakarta: Fakultas Kedokteran Universitas Negeri Surakarta; 2015. Fatima S, Braunberger T, Mohammad TF, Kohli I, Hamzavi IH. The Role of Sunscreen in Melasma and Postinflammatory Hyperpigmentation. Indian Journal of Dermatology. 2020;65(1):5-10. Sarkar R, Ghunawat S, Narang I, Verma SK, Garg VK, Dua R. Role of broad‐spectrum sunscreen alone in the improvement of melasma area severity index (MASI) and Melasma Quality of Life Index in melasma. Journal of Cosmetic Dermatology. 2019;18(4):1066-1073. Maymone MB, Neamah HH, Wirya SA, Patzelt NM, Zancanaro PQ, Vashi NA. Sun-protective behaviors in patients with cutaneous hyperpigmentation: A cross-sectional study. Journal of the American Academy of Dermatology. 2017;76(5):841-846.